2017 Spokane, Washington July 16 - July 19, 2017 2017
DOI: 10.13031/aim.201700583
|View full text |Cite
|
Sign up to set email alerts
|

<i>Effect of controlled traffic farming on energy saving in Australian grain cropping systems</i>

Abstract: Controlled traffic farming (CTF) is a system in which all machinery has the same or modular working and track widths so that field traffic can be confined to the least possible area of compacted permanent traffic lanes. In well-designed CTF systems permanent traffic lanes usually occupy less than 15% of cropped area, and this has been widely adopted in Australia. CTF is a practical and cost-effective facilitator of no-tillage farming, and the basis for more precise cropping systems. Controlled traffic systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
5
4
0
Order By: Relevance
“…This might be was due to the optimal moisture content during the implementation of the experiment in addition to the physics of clay soil, which has less resistance on the operational parts of the implement. This is consistent with the results obtained by [11] who confirmed that the soil type and moisture content have significant impacts on the mechanization indicators, particularly draught force. Rear tire pressure has less effects on the studied indicators, especially specific resistance and energy use efficiency (P>0.05), whereas this factor was significantly effects on draught force and soil resistance to cutting and shaping (P<0.05), where less tire pressure resulted higher draught force (2.35 vs. 2.17 kN) as the ground contact area is responding negatively with tire pressure.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This might be was due to the optimal moisture content during the implementation of the experiment in addition to the physics of clay soil, which has less resistance on the operational parts of the implement. This is consistent with the results obtained by [11] who confirmed that the soil type and moisture content have significant impacts on the mechanization indicators, particularly draught force. Rear tire pressure has less effects on the studied indicators, especially specific resistance and energy use efficiency (P>0.05), whereas this factor was significantly effects on draught force and soil resistance to cutting and shaping (P<0.05), where less tire pressure resulted higher draught force (2.35 vs. 2.17 kN) as the ground contact area is responding negatively with tire pressure.…”
Section: Resultssupporting
confidence: 93%
“…Where the clay soil with no traffic achieved the best values of draught force, specific resistance, energy use efficiency as well as soil resistance to cutting and shaping (1.09 kN, 24.1 kN m -2 , 41.1 m 3 Mj -1 , 1.35 kN, respectively). The results were clearly confirmed that soil compaction induced by traffic of farming machinery had major impacts on all mechanization indicators which affected by the soil physical properties [11]. 4 described the effects of the interaction between rear tire pressure and number of traffics on the studied indicators.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Use of RTK-GPS (Real Time Kinematic Global Position System) technology provides errors in positional accuracy to less than 20 mm, making it possible to drive farm vehicles on the same permanent traffic lanes every year, leaving the crop zones in between free of traffic and the risk of compaction (Gasso et al, 2013;Bochtis et al, 2010;Raper, 2005). Compacted permanent traffic lanes also improve energy use efficiency (by reducing wheel slip and rolling resistance) and have even made it possible to start work in fields after heavy rainfall at an earlier stage than would be possible if the compacted lanes were not in place (Taylor, 1994;McPhee et al, 1995;Dickson and Ritchie, 1996;Tullberg, 2000;Luhaib et al, 2017). Bell et al (2003) have suggested that the greatest benefits of CTF systems are achieved when the width of all track gauges match, that is, when the distance from wheel centre to wheel centre across all equipment is the same.…”
Section: Measuring Soil Compaction and Its Effectsmentioning
confidence: 99%
“…Furthermore, farm machinery weights have increased significantly over time, with some agricultural machines weighing 2 Mega-grams in 1940 and 40 Mega-grams at the present time [2]. [3].For example, the weight of agricultural harvesters increased by approximately 65% between 1989 and 2009; as for tractors, their weight increased from 1.5 Megagrams in 1960 to 4 Mega-grams in 2000, which corresponds to an annual increase of 0.06 Megagrams, or an additional 1 Mega-grams every 17 years [4]. This increase in the weights of agricultural machines and the number of them passes within the field led to an increase in soil compaction levels IOP Publishing doi:10.1088/1755-1315/1214/1/012052 2 and negatively affected on the main soil functions [5].…”
Section: Introductionmentioning
confidence: 99%